Pengaruh Model Problem Based Learning (PBL) Terhadap Hasil Pembelajaran IPS Siswa Di SDN Kota Padang - Ginting, Ivan Immanuel; Zuardi, Zuardi; Mansurdin, Mansurdin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2019)
This research aims at finding out the effect of applying the Problem Based Learning (PBL) model toward the students’ learning outcomes of Social Sciense subject at Class IV of SDN 10 Lubuk Kilangan, Padang. This quasi experiment used the non-equivalent control group design. The population was all  grade student of the school in which IV A acted as the control class and IV B as the experiment one. The research result shows that there are effects of applying the model towerd the students’ learning outcomes. By using t-test with the level of significant of 0.05, it is found that tcount= -3.434 with P-Value of 0.001. Since the score of the P-Value is lower than  = 0.05, the H1 hypothesis is accepted.